Odpowiedź :
a) 2x + 1 = 9 - 2x dla x = 2
2 x 2 + 1 = 9 - 2 x 2
4 + 1 = 9 - 4
5 = 5
0 = 0
L = P
Odp.: Tak, spełnia równanie
b) 3(2x - 5) = 1 - 4x dla x = 1[tex]\frac{1}{2}[/tex]
6x - 15 = 1 - 4x
6 x 1[tex]\frac{1}{2}[/tex] - 15 = 1 - 4 x 1[tex]\frac{1}{2}[/tex]
6 x [tex]\frac{3}{2}[/tex] - 15 = 1 - 4 x [tex]\frac{3}{2}[/tex]
9 - 15 = 1 - 6
-6 = -5
L [tex]\neq[/tex] P
Odp.: Nie, nie spełnia równania
c) 4(y-6) - 3y = 2(y-9) dla y = -6
4y - 24 - 3y = 2y - 18
y - 24 = 2y - 18
-6 -24 = 2 x -6 -18
-30 = -12 -18
-30 = -30
0 = 0
L = P
Odp.: Tak, spełnia równanie
Odpowiedź:
a) 2x+1 = 9-2x
2x+2x = 9-1
4x = 8 / : 4
x = 2
TAK
b) 3 ( 2x-5) = 1-4x
6x-15 = 1-4x
6x+4x = 1+15
10x = 16 /: 10
x = [tex]\frac{8}{5}[/tex] x = 1 [tex]\frac{3}{5}[/tex]
NIE
c) 4(y-6)-3y = 2(y-9)
4y-24 = 2y-18
y-2y = - 18 +24
-y = -18 + 24
-y = 6
y = -6
TAK
Szczegółowe wyjaśnienie: